Atomic Absorption Spectrophotometric Determination of Trace Amounts of Arsenic and Some Heavy Metals in Their Treatment Technology by Iron Powder - Thi Kim Giang, Pham; Xuan Thu, Dang; Viet Quy, Ho (Asian Journal of Chemistry, 2013)
Arsenic and heavy metals present in wastewater were determined before and after treatment on the adsorbent column is significant science in Vietnam. In this study, we used the available natural materials, it is powdered and Fe(0) yellow sand, MnO2 powder under the granules used as adsorbent in the column. The survey materials were examined by X-ray diffraction (XRD), scanning electron microscopy (SEM). These study showed that the material consists of magnetite Fe3O4 38.18 %, hematite Fe2O3 12.73 %, wuestite FeO 16.36 % of the beneficial minerals for the adsorption of heavy metals. The results showed that the material can remove As and some heavy metals out of the environment, in particular: arsenic adsorption capacity (169.65 mg/kg) and some metals such as Mn, Fe, Cu, Pb, Cd, respectively: 6616.05, 6664.24, 426.07, 143.06 and 120.21 mg/kg and maintained for a period of 4 days. This shows good potential applications of sand and iron powder Fe(0) in the treatment of heavy metal pollution by column adsorption method.